Assessing the Complementarity of Preferential Tax Regimes in the Sakhalin Region - Vladimir V. Gromov (Financial Journal, 2023)
State regulation of the anthropogenic impact on nature, including the policy of limiting greenhouse gas emissions, makes it necessary to support those enterprises that are willing to invest in climate projects. The relevance of incentives in this field is confirmed by the task set by the Arctic Council chaired by Russia at the Research and Training Conference on Climate Change and Permafrost Thawing 2023, namely to find reasonable, practical solutions for adapting the global economy to such changes. In the area of taxation, there is a solution prepared by the Russian Ministry of Economic Development willing to provide a package of tax benefits for investors. According to the draft, they should be exempted from paying VAT and income tax. At the same time, the variety of previously introduced preferential ‘investment’ tax regimes calls into question the rationality of new tax incentives due to the assumption of their redundancy. The fact is that they have similarities in the basic idea of support aimed at the growth of regional investment activity. For this reason, the purpose of the article is to answer the following questions: Is it really worthwhile to expand the number of tax regimes once again? Is it possible to use existing incentives instead of introducing new ones? To achieve the purpose, we rely on the results of comprehensive, comparative analysis of the developed incentives and the current tax preferential regimes on the example of the Sakhalin region. It stands out among other regions of Russia by its carbon-neutral pilot project and the greater number of preferences already enjoyed by investors, so we can provide representative and practically significant results. The hypothesis of the study is based on the concept of complementarity, meaning that the newly developed tax incentives will contribute to the complexity of the Russian tax system but will not cross the scope of the other mentioned tax regimes. The results show that climate projects have their own specifics in terms of objectives as well as ...